(untitled) (Research, Society and Development, 2022)
Congenital anomalies are malformations observed in prepartum or after birth. They significantly impact infant mortality rates and represent a public health problem. The study aims to evaluate the impact of the implementation of a fully Paraíba telemedicine network on local epidemiology related to congenital malformations, comparing them to worldwide incidences. It is a retrospective descriptive study, based on the records of births and malformations, for two years (2018 and 2019). The incidence of the study was accounted for by 11.815 patients, of which 476 presented malformation, while the continental incidences were collected from the literature. The statistical analysis of the data was performed by the T-Test and the One-way ANOVA test. There was a predominance of cardiac (30%), musculoskeletal (15%) and genito-urinary tract (13.9%) malformations. The statistical comparison of the malformations in Paraíba with the continental data reflected similarity with the Asian (p-value = 0,03037), African (p-value = 0,03327) and European (p-value = 0,04787) continents. The comparison of the population averages measured that the data of Paraíba, tied to the world data, is statistically within an acceptable pattern (p-value = 0,041638). The high incidence of malformations reported is possibly due to the local screening methods adopted associated with the telemedicine adopted by the Rede Cuidar. The similarity with developing continents denotes a reality of the impact of anomalies in these countries. The study was limited to the collection of continental data, related to the publication period of the selected studies and the grouped malformations.